Dydona pisze do Eneasza - Wesołowska, Elżbieta (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
The article presents a poetic translation into Polish of Ovid’s Heroides VII and includes an interpretation and notes on the text.
Keywords: Owidiusz; Heroidy; Wergiliusz; Eneida; mitologia rzymska; Eneasz; Dydona